The effect of warm water compresses on gout pain in the elderly at Takalar Community Health Center Makassar - Julianti, Hardiana; Nawawih, Aswan (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Gout arthritis, commonly referred to as gout, is a chronic non-communicable disease characterized by joint inflammation caused by elevated uric acid levels. This condition can persist for years or even a lifetime, leading to recurrent pain. One non-pharmacological treatment for managing gout pain is the application of warm water compresses, which may help alleviate discomfort by improving blood circulation and reducing inflammation. Purpose: This study aimed to assess the effectiveness of warm water compresses in reducing gout-related pain in elderly patients. Methods: The study used a quasi-experimental design with a control group and a pretest-posttest approach. A total of 32 elderly respondents suffering from gout pain at Takalar Community Health Center Makassar, were selected through purposive sampling. Pain levels were measured before and after the intervention using standardized pain scales. An independent t-test was conducted to analyze the differences between the experimental and control groups. Results: The independent t-test revealed a statistically significant effect of warm water compresses on reducing gout pain, with a p-value of 0.00 (p < 0.05). This indicates that warm water compresses effectively alleviate gout-related pain in the elderly. Conclusion: Warm water compresses significantly reduce gout pain in elderly patients at Takalar Community Health Center, Makassar. These findings suggest that warm water compresses can be a simple, non-invasive, and effective treatment option for managing gout pain in older adults.